2016
DOI: 10.1016/j.reprotox.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of epilepsy in pregnancy: The neurodevelopmental risks associated with exposure to antiepileptic drugs

Abstract: A number of antiepileptic drugs (AEDs) have been confirmed as teratogens due to their association with an increased malformation rate. The majority of research to date does not find an association between prenatal exposure to monotherapy carbamazepine, lamotrigine or phenytoin and neurodevelopmental outcome in comparison to control children and noted higher abilities in comparison to children exposed to valproate; but further work is needed before conclusions can be drawn. Data for levetiracetam was limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 100 publications
1
14
0
Order By: Relevance
“…Our findings are in accordance with previous studies, which found prenatal valproate exposure to be associated with high risk of poor neurodevelopment in infancy and childhood 33. Furthermore, a higher risk of adverse outcomes in the children has been found for higher doses of valproate exposure 34. We have no explanation for the finding of a higher risk of GP contact for prenatal exposure to low dose, but not high dose, of oxcarbazepine.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in accordance with previous studies, which found prenatal valproate exposure to be associated with high risk of poor neurodevelopment in infancy and childhood 33. Furthermore, a higher risk of adverse outcomes in the children has been found for higher doses of valproate exposure 34. We have no explanation for the finding of a higher risk of GP contact for prenatal exposure to low dose, but not high dose, of oxcarbazepine.…”
Section: Discussionsupporting
confidence: 92%
“…For example, we found a possible risk increase associated with carbamazepine and clonazepam, which has not been previously described. 20 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Exposure to epilepsy related factors during pregnancy may further increase the risk of ADHD, over and above familial transmission. Intrauterine exposure to certain antiepileptic drugs has been associated with an increased risk of adverse neurodevelopmental outcomes, whereas evidence for a similar risk linked to seizures during pregnancy is less clear (39). Results have also been interpreted as suggestive of maternal-specific genetic transmission, however there is currently only limited evidence for such a parent-of-origin effect (40).…”
Section: Discussionmentioning
confidence: 99%